Organizational Involvement in Higher Education as a Predictor of Students’ Soft Skills - Hadi Sulistyanto, Tri; Ghina , Azzahra; Hanny , Handiani; Dewi , Apriliani; Eva, Apriliani; Ela , Nurlela (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
This study aims to examine the effect of student involvement in Student Activity Units (UKM) on the development of soft skills. A quantitative approach using the survey method was employed in this research. The research population consisted of 455 fourth-semester students from STIE Wibawa Karta Raharja (Wikara Business School). The sample was determined using the Slovin formula with a 5% margin of error. Data were collected using a questionnaire based on a 1–5 Likert scale, which was distributed online via Google Forms. The independent variable is student involvement in UKM, assessed through three indicators: participation level, duration of involvement, and organizational membership status. The dependent variable is soft skills, encompassing seven dimensions: public speaking, entrepreneurship, teamwork, leadership, problem solving, critical and creative thinking, and time management. The test results indicate that student activity in UKM has a significant effect on soft skills, with a path coefficient of 0.679 and a p-value of 0.000. The R-square value of 0.371 suggests that student activities account for 37.1% of the variance in soft skills, while the f-square value of 0.590 indicates a strong effect size. The strongest indicators of soft skills development are public speaking, problem-solving, and leadership. These findings suggest that active involvement in student organizations (UKM) can serve as a strategic means to enhance students’ non-technical skills, which are essential for success in the professional world. Therefore, educational institutions should continue to promote and support active participation in such organizations.